COEFFICENT INVERSE PROBLEM FOR SOLUTE TRANSPORT IN A CYLINDRICAL NON-HOMOGENEOUS POROUS MEDIUM - Sulaymonov, Fozil (Журнал математики и информатики, 2020)
In several works the sape of the medium is defined, such as cylinder, sphere, plate-layered medium etc. In one of them two coaxial cylinders are used, the intrinsic one ha relatively higher filtration-capacity properties (macrapore), and surrounding one-relatively less properties (micropore). As a rule two approaches are used: diffusional and kinetic.